Verbal and non-verbal skills in early childhood: dimensionality, developmental trajectories, and gender differences - Elnes, Magdalena; Hansen, Joakim Evensen; Lervåg, Arne; Hatlevik, Ove Edvard; Reikerås, Elin Kirsti Lie (Frontiers in Psychology, 2024)
This study examines the dimensionality of and relationships between two subscales from the British Ability Scales – Third Edition, measuring verbal (expressive vocabulary) and non-verbal (reasoning) cognitive skills for toddlers (age three) and preschoolers (age five), in a Norwegian context across genders. Descriptive statistics revealed item selection criteria that included specific items within each subscale. Subsequently, Confirmatory Factor Analysis established the subscales’ dimensionality (Naming Vocabulary and Picture Similarities; N = 1094) and confirmed measurement invariance across genders. Further, the relationships between the verbal and non-verbal factors were investigated using correlation analysis and Structural Equation Modeling. The findings revealed that the verbal factor at age three strongly predicted the verbal factor at age five and significantly influenced the non-verbal factor at age five. The non-verbal factor at age three exhibited a moderate predictive relationship with the non-verbal factor at age five, and did not significantly predict the verbal factor at age five. In terms of gender differences, girls showed higher scores on the verbal factor at age three, and a stronger correlation between the non-verbal factor at age three and the verbal factor at age five. In summary, this research provides valuable insights into cognitive skill measurement and development in a Norwegian context and highlights possible variations across gender. The study’s findings, limitations, and implications are discussed.